Detecting and Characterizing Exoplanets with Direct Imaging: Past, Present, and Future. Issue Volume 8:Issue S299(2013) (6th January 2014) - Biller, Beth
Abstract: The last decade has yielded the first images of exoplanets, considerably advancing our understanding of the properties of young giant planets. In this talk I will discuss current results from ongoing direct imaging efforts as well as future prospects for detection and characterization of exoplanets via high contrast imaging. Direct detection, and direct spectroscopy in particular, have great potential for advancing our understanding of extrasolar planets. In combination with other methods of planet detection, direct imaging and spectroscopy will allow us to eventually: 1) study the physical properties of exoplanets (colors, temperatures, etc.) in depth and 2) fully map out the architecture of typical planetary systems. Direct imaging has offered us the first glimpse into the atmospheric properties of young high-mass (3-10 M Jup ) exoplanets. Deep direct imaging surveys for exoplanets have also yielded the strongest constraints to date on the statistical properties of wide giant exoplanets. A number of extremely high contrast exoplanet imaging instruments have recently come online or will come online within the next year (including Project 1640, SCExAO, SPHERE, GPI, among others). I will discuss future prospects with these instruments.